Asymmetric monetary transmission in EMU : the robustness of VAR conclusions and Cecchettis legal family theory - Adam Elbourne; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2004)
We review studies on monetary transmission in the EU countries using the VAR approach and analyse why they often lead to divergent outcomes. Firstly, we estimate 43 VAR models across ten EU countries and compare the robustness of the ranking of the magnitudes of the price and output responses. The main specification differences between the VAR models are the use of two different sample periods; the inclusion of additional variables; and the use of recursive, long run, and structural identification schemes. Secondly, we calculate rank correlations between the output and price responses of a recursive VAR and a structural VAR to the financial structure indicators used by Cecchetti (1999), who argued that legal systems cause financial structure, which in turn causes asymmetric transmission. In contrast to Cecchetti, we find that there is little correlation.
Keywords: E52; 330; monetary transmission; VAR models; EMU; Transmissionsmechanismus; VAR-Modell; Bankensystem; Finanzsektor; Schätzung; EU-Staaten